Implementation of Merdeka Curriculum Learning Management at SMPN 1 Bastem - Hadijah Hadijah; Wisran Wisran; Bustanul Iman Bustanul Iman (International Journal of Educational Administration, Management, and Leadership, 2024)
This study explores the implementation of learning management in the Kurikulum Merdeka framework at SMP Negeri 1 Bastem, a junior high school located in a 3T (frontier, outermost, disadvantaged) area of Luwu Regency, South Sulawesi. Using a qualitative embedded case study design, data were collected through observation, semi-structured interviews with the principal, vice principal for curriculum, and subject teachers, as well as document analysis of KOSP, teaching modules, and project modules. Data were analyzed using the interactive model of data condensation, data display, and conclusion drawing. The findings show that the management of Kurikulum Merdeka follows a relatively systematic cycle of planning, organizing, implementation, and evaluation. Planning is reflected in the preparation of the Kurikulum Operasional Satuan Pendidikan, development of differentiated teaching and project modules, and the use of the Merdeka Mengajar Platform. Organizing appears in the allocation of 20–30% lesson hours for project-based learning and the determination of local content in the form of regional language subjects to strengthen local wisdom. Implementation combines differentiated intrakurikuler learning with kokurikuler Projek Penguatan Profil Pelajar Pancasila using themes of local wisdom, engineering and technology, and entrepreneurship. Evaluation is conducted through diagnostic, formative, and summative assessments followed by remedial and enrichment programs. The study also identifies key challenges, including uneven teacher readiness, limited training and facilities, and students’ low learning autonomy, while highlighting the school’s adaptive strategies through collegial collaboration and contextual innovation in managing Kurikulum Merdeka.